2021
DOI: 10.3390/pharmaceutics13050713
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Metabolite Profile, Biological Activity and Overall Quality of Three Lettuce (Lactuca sativa L., Asteraceae) Cultivars in Response to Sulfur Nutrition

Abstract: The main objective of the present study was to assess the effects of sulfur (S) nutrition on plant growth, overall quality, secondary metabolites, and antibacterial and radical scavenging activities of hydroponically grown lettuce cultivars. Three lettuce cultivars, namely, Pazmanea RZ (green butterhead, V1), Hawking RZ (green multi-leaf lettuce, V2), and Barlach RZ (red multi-leaf, V3) were subjected to two S-treatments in the form of magnesium sulfate (+S) or magnesium chloride (−S). Significant differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 67 publications
6
30
0
1
Order By: Relevance
“…The foliar application at a concentration of 0.119 mg plant −1 (Se2) accumulated 4.1-4.9 μg Se g −1 DM in the green lettuce (V1), and 3.3-4.7 μg Se g −1 DM in the red lettuce (V2). This is consistent with our recently published findings [21], where the green multi-leaf lettuce (V1) demonstrated superior crop productivity compared to the red multi-leaf (V2).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…The foliar application at a concentration of 0.119 mg plant −1 (Se2) accumulated 4.1-4.9 μg Se g −1 DM in the green lettuce (V1), and 3.3-4.7 μg Se g −1 DM in the red lettuce (V2). This is consistent with our recently published findings [21], where the green multi-leaf lettuce (V1) demonstrated superior crop productivity compared to the red multi-leaf (V2).…”
Section: Resultssupporting
confidence: 93%
“…The lowest recorded yield, DM, and number of leaves were observed in the red lettuce (V2) grown under Se3 level in comparison to green lettuce (V1) grown under Se3 treatment (Figure 2A-C). This is consistent with our recently published findings [21], where the green multileaf lettuce (V1) demonstrated superior crop productivity compared to the red multi-leaf (V2).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The leaf extract, which contained a low lactucin concentration, showed weaker or no antibacterial activity. Thus, the antibacterial activity of the tissue extracts could be attributed to the presence of lactucin; however, as reported by previous studies, diverse sesquiterpenoids, phenolic, flavonoids, and minerals are also present in the crude extract and could potentially have an antibacterial effect (Nishimura et al 1986;Kim et al 2008;Michalska et al 2009;Kim and Yoon 2014;Padilla-Gonzalez et al 2016;Ha et al 2017;Abdalla et al 2021). A previous study by Pavlović et al (2011) showed that the extracts of Lactuca sativa grown in greenhouses showed high antibacterial activity against various bacterial strains, particularly against Staphylococcus aureus and Proteus mirabilis.…”
Section: Discussionmentioning
confidence: 87%